Spectral Evolution of an Eruptive Polar Crown Prominence With IRIS Observations - Xue , Jianchao; Li , Hui; Su , Yang (Frontiers in Physics, 2021)
Prominence eruption is closely related to coronal mass ejections and is an important topic in solar physics. Spectroscopic observation is an effective way to explore the plasma properties, but the spectral observations of eruptive prominences are rare. In this paper we will introduce an eruptive polar crown prominence with spectral observations from the Interface Region Imaging Spectrograph (IRIS), and try to explain some phenomena that are rarely reported in previous works. The eruptive prominence experiences a slow-rise and fast-rise phase, while the line-of-sight motions of the prominence plasma could be divided into three periods: two hours before the fast-rise phase, opposite Doppler shifts are found at the two sides of the prominence axis; then, red shifts dominate the prominence gradually; in the fast-rise phase, the prominence gets to be blue-shifted. During the second period, a faint component appears in Mg II k window with a narrow line width and a large red shift. A faint region is also found in AIA 304 ˚A images along the prominence spine, and the faint region gets darker during the expansion of the spine. We propose that the opposite Doppler shifts in the first period is a feature of the polar crown prominence that we studied. The red shifts in the second period is possibly due to mass drainage during the elevation of the prominence spine, which could accelerate the eruption in return. The blue shifts in the third period is due to that the prominence erupts toward the observer. We suggest that the faint component appears due to the decreasing of the plasma density, and the latter results from the expansion of the prominence spine.